Enhanced the thermal conductivity of flexible copper foil by introducing graphene - Jiao Li; Ping Zhang; Hong He; Bo Shi (Materials & Design, 2020)
Owing to the miniaturization, portability and wearable of electronic devices, the demand for advanced thermal management materials has increased significantly, especially for highly thermally conductive materials. In this paper, a simple and effective strategy for synthesizing high thermal conductivity copper-graphene (Cu-rGO) was proposed. The microstructure, thermal properties and thermal management capabilities of the composite film were studied. It was found that the obtained Cu-rGO film exhibits excellent flexibility and high thermal conductivity (637.7 W m−1 K−1). It indicates that the introduction of graphene effectively enhances the thermal conductivity of Cu matrix. Besides, the experimental results show that the Cu-rGO film has a lower coefficient of thermal expansion (CTE) and excellent heat transfer properties. This work provides important guidance for the preparation of high thermal conductivity composites that meet the growing heat dissipation requirements in the future. Keywords: Graphene/copper composite film, Thermal conductivity, Electrophoretic deposition, Vacuum hot pressing